Improving mental health following multiple disasters in Australia: a randomized controlled trial of the Skills for Life Adjustment and Resilience (SOLAR) programme - S. Cowlishaw; K. Gibson; S. Alexander; A. Howard; J. Agathos; S. Strauven; K. Chisholm; J. Fredrickson; L. Pham; W. Lau; M. L. O’Donnell (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground: The mental health impacts of climate change-related disasters are significant. However, access to mental health services is often limited by the availability of trained clinicians. Although building local community capability for the mental health response is often prioritised in policy settings, the lack of evidence-based programs is problematic. The aim of this study was to test the efficacy of the Skills for Life Adjustment and Resilience programme (SOLAR) delivered by trained local community members following compound disasters (drought, wildfires, pandemic-related lockdowns) in Australia.Method: Thirty-six community members were trained to deliver the SOLAR programme, a skills-based, trauma informed, psychosocial programme. Sixty-six people with anxiety, depression and/or posttraumatic stress symptoms, and impairment were randomised into the SOLAR programme or a Self-Help condition. They were assessed pre, post and two months following the interventions. The SOLAR programme was delivered across five 1-hourly sessions (either face to face or virtually). Those in the Self-Help condition received weekly emails with self-help information including links to online educational videos.Results: Multigroup analyses indicated that participants in the SOLAR condition experienced significantly lower levels of anxiety and depression, and PTSD symptom severity between pre – and post-intervention (T1 to T2), relative to the Self-Help condition, while controlling for scores at intake. These differences were not statistically different at follow-up. The SOLAR programme was associated with large effect size improvements in posttraumatic stress symptoms over time.Conclusion: The SOLAR programme was effective in improving anxiety, depression and posttraumatic stress symptoms over time. However, by follow-up the size of the effect was similar to an active self-help condition. Given the ongoing stressors in the community associated with compounding disasters it may be that booster sessions would have been useful to sustain programme impact.Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12621000283875..